1992
DOI: 10.1073/pnas.89.13.6015
|View full text |Cite
|
Sign up to set email alerts
|

Rapid fitness losses in mammalian RNA virus clones due to Muller's ratchet.

Abstract: Muller's ratchet is an important concept in population genetics. It predicts that when mutation rates are high and a significant proportion of mutations are deleterious, a kind of irreversible ratchet mechanism will gradually decrease the mean fitness of small populations of asexual organisms. In contrast, sexual recombination may stop or reverse this mutational ratchet by recombinational repair Muller (1) suggested that accumulation of deleterious mutations in asexual (2) organisms occurs by "a kind ofirrev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
305
1
5

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 319 publications
(328 citation statements)
references
References 21 publications
17
305
1
5
Order By: Relevance
“…It is too early to suggest whether effects of m.o.i., such as those we have described, might be common with other FMDV mutants or with other viruses. However, the results that we have obtained indicate that in competition assays it will be necessary to adjust the initial mixtures to a standard m.o.i., as was done in the fitness determinations with VSV (Holland et al, 1991 ;Duarte et al, 1992 ;Clarke et al, 1993Clarke et al, , 1994, although in this case this precaution was prompted by the need to avoid accumulation of defective-interfering particles. Some effects of frequency-dependent selection in VSV (Elena et al, 1997) could have been influenced by m.o.i.-dependence of relative fitness between two competing viruses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is too early to suggest whether effects of m.o.i., such as those we have described, might be common with other FMDV mutants or with other viruses. However, the results that we have obtained indicate that in competition assays it will be necessary to adjust the initial mixtures to a standard m.o.i., as was done in the fitness determinations with VSV (Holland et al, 1991 ;Duarte et al, 1992 ;Clarke et al, 1993Clarke et al, , 1994, although in this case this precaution was prompted by the need to avoid accumulation of defective-interfering particles. Some effects of frequency-dependent selection in VSV (Elena et al, 1997) could have been influenced by m.o.i.-dependence of relative fitness between two competing viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic studies on the dynamics of fitness variations with RNA viruses have established that repeated genetic bottlenecks (experimentally realized by serial plaque-to-plaque virus transfers) result in average fitness losses (Chao, 1990 ;Duarte et al, 1992 ;Escarmı! s et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Res. 1,[2][3][4][5][6][7][8][9]. The operation of Muller's ratchet on real populations has been experimentally demonstrated only in RNA viruses.…”
Section: Introductionmentioning
confidence: 99%
“…(ii) Chao (7) showed that the RNA virus 46, when propagated asexually under intense genetic drift, accumulated deleterious mutations resulting in loss of viability. (iii) Similarly, others (8,9) have shown that vesicular stomatitis virus (VSV) lost fitness when genetic bottlenecks were introduced during virus propagation. Chao et al (10) showed that recombination between mutant 46 lineages could restore viability almost to the wild-type level, demonstrating how sex can slow down the ratchet.…”
mentioning
confidence: 98%
“…This diversification may lead to fitness losses due to the buildup of deleterious mutations or to rapid and unpredictable fitness gains (7,11). Although this genetic variation is ultimately produced by mutation, it also could be shaped by natural selection, most likely from two sources.…”
mentioning
confidence: 99%